-6x+5y=1
Solve for x
Move variable to the right side and change its sign: +5y
-6x=1-5y
Divide both sides of the equation by -6
-6x=1-5y
-6 -6
x=-1/6+5/6y
Substitute the given value of x into the equation 6x+4y=-10
6(-1/6+5/6y)+4y=-10
Solve for y
Distribute 6 through the parenthesis: 6(-1/6+5/6y)
-1+5y+4y=-10
Collect the like terms: 5y+5y
-1+9y=-10
Move constant to the right side and change its sign: -1
9y=-10+1
Calculate the sum or difference: -10+1
9y=-9
Divide both sides of the equation by 9
9y=-9
-9 -9
y=-1
Substitute the given value of y into the simplest equation: 6x+4y=-10
6x+4*(-1)=-10
Any expression multiplied by -1 equals its opposite: 4*(-1)
6x-4=-10
Move constant to right and change sign: -4
6x=-10+4
Calculate sum or difference: -10+4
6x=-6
divide both sides by 6
6x=-6
6 6
x=-1
The solution of the system is the ordered pair (x,y)
(x,y)=(-1,-1)
Check if the given ordered pair is the solution of the system of equations
-6*(-1)+5*(-1)=1
6*(-1)+4*(-1)=-10
Simplify the expression: -6*(-1)+5*(-1)=1
1=1
Simplify the expression: 6*(-1)+4*(-1)=-10
-10=-10
The ordered pair is the solution of the system of equations since both equations are true
(x,y)=(-1,-1)
HOPE THIS HELPS!!!